Designing of a conceptual framework for the obstacles to implementing e-learning in teaching chemistry in Nalut Libyan high schools - Al-Sifaw, Saeed Ahmed Saeed; Abdullah, Abdul Hakim (Journal of Educational and Psychological Sciences, 2020)
This study aimed to build a conceptual framework by investigating the critical factors that impede the application of e-learning in secondary schools in Nalut, Libya. The conceptual framework for this study was suggested by investigating the obstacles and difficulties that hinder the use of e-learning in general and based on previous studies to build the questionnaire for this study, this study was limited to the scientific section of government secondary schools in Nalut. The field study was conducted during the first semester of the academic year 2018-2019. Barriers that may constitute difficulties in employing e-learning using a quantitative approach have been studied using a questionnaire consisting of four areas (individual difficulties, context difficulties, technology difficulties, difficulties with the chemistry approach), and based on the results of the correlative and influential study of the questionnaire for the random sample that reached (724) among which are teachers, supervisors and students from the Libyan high schools Nalut Libyan, the conceptual framework for the study community was built, through descriptive analysis using statistical analysis spss version (21.0) to identify the degree of difficulties of e-learning in teaching chemistry, and on laboratories To link Pearson Pearson Test to identify the degree of correlation between all the difficulties as well as the study used regression analysis Multiple Multiple Regression Analysis to identify the impact strength of difficulties. The study, which was derived from the analysis of the survey data, found a correlation between the difficulties of (contexts, technology and curriculum) and individual difficulties, and the presence of an influence correlation between the difficulties of each (contexts, technology and curriculum) and individual difficulties. The proposed conceptual framework for this study contributes to knowing the obstacles of e-learning by creating a guide for educational institutions and governments in order to develop and implement better, and it works as a tool to avoid the failure of implementing new e-learning projects through planning that meets the attitudes and tendencies of individuals towards the effective use of e-learning and as a method of evaluating the effectiveness of projects Current e-learning.